Changes in the structure, digestibility and immunoreactivities of glycinin induced by the cross‐linking of microbial transglutaminase following heat denaturation. (18th June 2017) - Yang, Anshu; Xia, Jiaheng; Gong, Yuqing; Deng, Han; Wu, Zhihua; Li, Xin; Tong, Ping; Chen, Hongbing
Summary: This study aimed to evaluate the effects of microbial transglutaminase (MTG)‐mediated modification on the structure, digestibility and immunoreactivities of glycinin. Glycinin was separated from soya bean and cross‐linked with MTG, and the sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) showed that the molecular weight of cross‐linked glycinin was higher than that of native glycinin. Individual MTG cross‐linking could maintain stable secondary structures and spatial structure. Sequential heat denaturation and MTG cross‐linking could promote the unfolding of protein structures and reduce their hydrophobicity. The digestibility of glycinin was decreased, and its immunoreactivities were increased because of MTG‐induced structural alteration, including primary and spatial structures. Abstract : MTG‐mediated modification significantly reduces the IgE reactivity of glycinins.